Adding dimension to cellular mechanotransduction: Advances in biomedical engineering of multiaxial cell-stretch systems and their application to cardiovascular biomechanics and mechano-signaling. - Friedrich, Oliver; Schneidereit, Dominik; Nikolaev, Y. A.; Nikolova-Krstevski, V.; Schürmann, Sebastian; Wirth-Hücking, Anette; Merten, Anna-Lena; Fatkin, D.; Martinac, B. (Progress in biophysics and molecular biology, 2017)
Hollow organs (e.g. heart) experience pressure-induced mechanical wall stress sensed by molecular mechano-biosensors, including mechanosensitive ion channels, to translate into intracellular signaling. For direct mechanistic studies, stretch devices to apply defined extensions to cells adhered to elastomeric membranes have stimulated mechanotransduction research. However, most engineered systems only exploit unilateral cellular stretch. In addition, it is often taken for granted that stretch applied by hardware translates 1:1 to the cell membrane. However, the latter crucially depends on the tightness of the cell-substrate junction by focal adhesion complexes and is often not calibrated for. In the heart, (increased) hemodynamic volume/pressure load is associated with (increased) multiaxial wall tension, stretching individual cardiomyocytes in multiple directions. To adequately study cellular models of chronic organ distension on a cellular level, biomedical engineering faces challenges to implement multiaxial cell stretch systems that allow observing cell reactions to stretch during live-cell imaging, and to calibrate for hardware-to-cell membrane stretch translation. Here, we review mechanotransduction, cell stretch technologies from uni-to multiaxial designs in cardio-vascular research, and the importance of the stretch substrate-cell membrane junction. We also present new results using our IsoStretcher to demonstrate mechanosensitivity of Piezo1 in HEK293 cells and stretch-induced Ca(2+) entry in 3D-hydrogel-embedded cardiomyocytes.

IL-1α reversibly inhibits skeletal muscle ryanodine receptor a novel mechanism for critical illness myopathy? - Edwards, Joshua N.; Weber, Cornelia; Liu, Ilon; Reischl, Barbara; Most, Patrick; Wirth-Hücking, Anette; Yi, Bing; Friedrich, Oliver; Voelkers, Mirko; Buttgereit, Andreas; Lang, Roland; Lee, Aven; et al. (American journal of respiratory cell and molecular biology, 2014)
Critical illness myopathies in patients with sepsis or sustained mechanical ventilation prolong intensive care treatment and threaten both patients and health budgets; no specific therapy is available. Underlying pathophysiological mechanisms are still patchy. We characterized IL-1α action on muscle performance in "skinned" muscle fibers using force transducers and confocal Ca fluorescence microscopy for force/Ca transients and Ca sparks. Association of IL-1α with sarcoplasmic reticulum (SR) release channel, ryanodine receptor (RyR) 1, was investigated with coimmunoprecipitation and confocal immunofluorescence colocalization. Membrane integrity was studied in single, intact fibers challenged with IL-1α. IL-1α reversibly stabilized Mg inhibition of Ca release. Low Mg-induced force and Ca transients were reversibly abolished by IL-1a. At normal Mg , IL-1α reversibly increased caffeine-induced force and Ca transients. IL-1α reduced SR Ca leak via RyR1, as judged by (1) increased SR Ca retention, (2) increased IL-1α force transients being reproduced by 25 μM tetracaine, and (3) reduced Ca spark frequencies by IL-1a or tetracaine. Coimmunoprecipitation confirmed RyR1/IL-1 association. RyR1/IL-1 immunofluorescence patterns perfectly colocalized. Long-term, 8-hour IL-1α challenge of intact muscle fibers compromised membrane integrity in approximately 50% of fibers, and confirmed intracellular IL-1α deposition. IL-1α exerts a novel, specific, and reversible interaction mechanism with the skeletal muscle RyR1 macromolecular release complex without the need to act via its membrane IL-1 receptor, as IL-1R membrane expression levels were not detectable in Western blots or immunostaining of single fibers. We present a potential explanation of how the inflammatory mediator, IL-1α, may contribute to muscle weakness in critical illness. Copyright © 2014 by the American Thoracic Society.
Keywords: Critical illness myopathy; Cytokines; IL-1; Ryanodine receptor 1

Single fibre cytoarchitecture in ventilator-induced diaphragm dysfunction (VIDD) assessed by quantitative morphometry second harmonic generation imaging: Positive effects of BGP-15 chaperone co-inducer and VBP-15 dissociative corticosteroid treatment - Mnuskina, Sofia; Bauer, Julian; Wirth-Hücking, Anette; Schneidereit, Dominik; Nübler, Stefanie; Ritter, Paul; Cacciani, Nicola; Li, Meishan; Larsson, Lars; Friedrich, Oliver (Frontiers in Physiology, 2023)
Ventilator-induced diaphragm dysfunction (VIDD) is a common sequela of intensive care unit (ICU) treatment requiring mechanical ventilation (MV) and neuromuscular blockade (NMBA). It is characterised by diaphragm weakness, prolonged respirator weaning and adverse outcomes. Dissociative glucocorticoids (e.g., vamorolone, VBP-15) and chaperone co-inducers (e.g., BGP-15) previously showed positive effects in an ICU-rat model. In limb muscle critical illness myopathy, preferential myosin loss prevails, while myofibrillar protein post-translational modifications are more dominant in VIDD. It is not known whether the marked decline in specific force (force normalised to cross-sectional area) is a pure consequence of altered contractility signaling or whether diaphragm weakness also has a structural correlate through sterical remodeling of myofibrillar cytoarchitecture, how quickly it develops, and to which extent VBP-15 or BGP-15 may specifically recover myofibrillar geometry. To address these questions, we performed label-free multiphoton Second Harmonic Generation (SHG) imaging followed by quantitative morphometry in single diaphragm muscle fibres from healthy rats subjected to five or 10 days of MV + NMBA to simulate ICU treatment without underlying confounding pathology (like sepsis). Rats received daily treatment of either Prednisolone, VBP-15, BGP-15 or none. Myosin-II SHG signal intensities, fibre diameters (FD) as well as the parameters of myofibrillar angular parallelism (cosine angle sum, CAS) and in-register of adjacent myofibrils (Vernier density, VD) were computed from SHG images. ICU treatment caused a decline in FD at day 10 as well as a significant decline in CAS and VD from day 5. Vamorolone effectively recovered FD at day 10, while BGP-15 was more effective at day 5. BGP-15 was more effective than VBP-15 in recovering CAS at day 10 although not to control levels. In-register VD levels were restored at day 10 by both compounds. Our study is the first to provide quantitative insights into VIDD-related myofibrillar remodeling unravelled by SHG imaging, suggesting that both VBP-15 and BGP-15 can effectively ameliorate the structure-related dysfunction in VIDD.
CRIS-Team Scopus Importer:2023-08-25
Keywords: BGP-15; critical illness; diaphragm dysfunction; quantitative morphometry; second harmonic generation

The IsoStretcher: An isotropic cell stretch device to study mechanical biosensor pathways in living cells. - Schürmann, Sebastian; Wagner, Sören; Herlitze, Simon; Fischer, C.; Gumbrecht, S.; Wirth-Hücking, Anette; Prölß, Gerhard; Lautscham, Lena; Fabry, Ben; Goldmann, Wolfgang; Nikolova-Krstevski, V.; Martinac, B.; et al. (Biosensors and Bioelectronics, 2016)
Mechanosensation in many organs (e.g. lungs, heart, gut) is mediated by biosensors (like mechanosensitive ion channels), which convert mechanical stimuli into electrical and/or biochemical signals. To study those pathways, technical devices are needed that apply strain profiles to cells, and ideally allow simultaneous live-cell microscopy analysis. Strain profiles in organs can be complex and multiaxial, e.g. in hollow organs. Most devices in mechanobiology apply longitudinal uniaxial stretch to adhered cells using elastomeric membranes to study mechanical biosensors. Recent approaches in biomedical engineering have employed intelligent systems to apply biaxial or multiaxial stretch to cells. Here, we present an isotropic cell stretch system (IsoStretcher) that overcomes some previous limitations. Our system uses a rotational swivel mechanism that translates into a radial displacement of hooks attached to small circular silicone membranes. Isotropicity and focus stability are demonstrated with fluorescent beads, and transmission efficiency of elastomer membrane stretch to cellular area change in HeLa/HEK cells. Applying our system to lamin-A overexpressing fibrosarcoma cells, we found a markedly reduced stretch of cell area, indicative of a stiffer cytoskeleton. We also investigated stretch-activated Ca(2+) entry into atrial HL-1 myocytes. 10% isotropic stretch induced robust oscillating increases in intracellular Fluo-4 Ca(2+) fluorescence. Store-operated Ca(2+) entry was not detected in these cells. The Isostretcher provides a useful versatile tool for mechanobiolog